Between professionalism and political engagement in foreign language teaching practice. Issue 3 (19th August 2022) - Kramsch, Claire
Abstract : In this paper, I reflect on a project I conducted at University of California Berkeley with four colleagues teaching Chinese, Hebrew, Italian and Japanese who decided to engage their students in some of the political controversies in which the native speakers of these languages are engaged in their respective countries. These four teachers are highly educated, experienced native speakers, and they are all professional non-senate members of the faculty. Following the students' wishes they focused respectively on the following topics: racism against Asians in the US; the Israeli–Palestinian conflict; immigrant refugees to Italy from Muslim countries; and how to remember Hiroshima. Given the low level of language proficiency of their classes, the teachers' common professional practice was to elicit and capitalize on their students' emotional involvement. However, while the teachers engaged the learners emotionally into seeing these conflicts from the native speakers' perspective, they were hampered by their very professional practice from delving into the complex political meanings of the events discussed. I reflect on the reasons for this seeming lack of translingual activism and what it means for foreign language teaching as professional and political practice.